Molecular Biology View on Down syndrome: Review article - H Naser, Rana; Algburi, Ammar; Abdelhameed , Alyaa (Diyala Journal of Medicine, 2023)
Background: Down Syndrome (DS) is a resulting from a defect of the genotype in patients affected by it. The occurrence of this type of disease is very common. It has been associated with causing many genetic diseases with a significant change in phenotypic pattern. People with this type of disease suffer from intellectual disability that ranges from mild to moderate, delay in growth and the emergence of some distinctive signs in the face. It leads to Alzheimer’s in some cases. The treatment cost is very high and exorbitant, many laboratories have sophisticated diagnoses methods, but they are expensive and require high skill. Therefore, this disease still needs to develop many genetic methods to facilitate its diagnosis infection rates reduction among humans.The present review article empasied an overview of DS-associated phenotypes diagnosis and managment of the disease. Furthermore,we have also Reviewed further parental diagnosis methods to facilate moleculr methods CSV, MLPA, FISH, QF-PCR, PSQ, and NGS and noninvasive dignosis in details